Clear band formation simulated by dislocation dynamics - Nogaret, T.; Rodney, D.; Fivel, M.; Robertson, C. (Вопросы атомной науки и техники, 2009)
Dislocation Dynamics simulations of dislocations gliding across a random populations of Frank loops are presented. Specific local rules are developed to reproduce elementary interaction mechanisms obtained in Molecular Dynamics simulations. It is shown that absorption of Frank loops as helical turns on screw dislocations governs the process of clear band formation, because: (1) it transforms the loops into jogs on dislocations, (2) when the dislocations unpin, the jogs are transported along the dislocation lines, leading to a progressive clearing of the band and (3) the dislocations are re-emitted in a glide plane different from the initial one, allowing for a broadening of the band. It is also shown that a pile-up of dislocations is needed to form a clear band of finite thickness.